2018
DOI: 10.11606/s1518-8787.2018052000394
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic context of the community and chronic child malnutrition in Colombia

Abstract: OBJECTIVE To analyze the influence of the socioeconomic context of the community on chronic child malnutrition in Colombia.METHODS We estimated multilevel logistic models using data from the National Demographic and Health Survey in Colombia in 2010. The final sample included 11,448 children under the age of five gathered in 3,528 communities. In addition, we used the Principal Component Analysis with polychoric correlations for the construction of composed indicators of wealth, autonomy of the woman, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
0
20
0
10
Order By: Relevance
“…Naz et al (2014) discuss that while women self-report high levels of participation in household food and nutrition security, few are satisfied with their decision-making power in the household. Osorio et al (2018) find that in Colombia, women's autonomy is associated with lower levels of chronic child malnutrition. Mukhergee and Kundu (2012) find in West Bengal, India, that men continue to dominate, especially in household money management decisions, even though women's participation in self-help micro-credit groups increased their participation in household decision-making.…”
Section: Decision-makingmentioning
confidence: 77%
“…Naz et al (2014) discuss that while women self-report high levels of participation in household food and nutrition security, few are satisfied with their decision-making power in the household. Osorio et al (2018) find that in Colombia, women's autonomy is associated with lower levels of chronic child malnutrition. Mukhergee and Kundu (2012) find in West Bengal, India, that men continue to dominate, especially in household money management decisions, even though women's participation in self-help micro-credit groups increased their participation in household decision-making.…”
Section: Decision-makingmentioning
confidence: 77%
“…The probability is 63.7% when the child belongs to a household with a low standard of living, all other things being equal [20]. More recent work by Ossorio et al, (2018), has confirmed the association between standard of living in the household and malnutrition, according to the author, at the level of individuals and households, the probability of malnutrition [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have studied the determinants of malnutrition. According to OSORIO, Ana María et al [5], the context in which the children live affects their health, regardless of the characteristics of the children, their mother, and their household. Communities share physical, social, and economic attributes that may be fundamental to improve the health condition of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to this, many studies have shown how SES influences the adequate fulfilment of processes related to physical, emotional, and cognitive development [ 8 , 9 ]. Additionally, low-SES is associated with malnutrition [ 10 , 11 ]. According to the United Nations Children’s Fund (UNICEF) [ 12 ], globally, poor nutrition negatively impacts the development in one out of every three children.…”
Section: Introductionmentioning
confidence: 99%